Piety and politics Islamism in contemporary Malaysia - Liow, Joseph Chinyong, 1972- (Oxford : Oxford University Press, 2009)
Malaysia, home to some 20 million Muslims, is often held up as a model of a pro-Western Islamic nation. The government of Malaysia, in search of Western investment, does its best to perpetuate this view. This book offers a comprehensive analysis of the growing role of Islam in the last quarter century of Malaysian politics.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United Malays National Organisation; Islam and politics -- Malaysia; Islam and state -- Malaysia; Islamic fundamentalism -- Malaysia; Malaysia -- Politics and government